The Molecular Mechanisms That Underlie the Immune Biology of Anti-drug Antibody Formation Following Treatment With Monoclonal Antibodies - Vaisman-Mentesh, Anna; Gutierrez-Gonzalez, Matias; DeKosky, Brandon J.; Wine, Yariv (Frontiers in Immunology, 2020)
While monoclonal antibodies (mAbs) offer tremendous benefits for improving human health, the repeated administration of mAbs can be highly immunogenic. Drug immunogenicity is mostly manifested by the generation of anti-drug antibodies (ADA), and some mAbs show immunogenicity in up to 70% of patients. ADA can alter a drug’s pharmacokinetic and pharmacodynamic properties and reduce drug efficacy, and in more severe cases they can neutralize the drug’s therapeutic effects or cause severe adverse events to the patient. While some contributing factors to ADA formation are known, the molecular mechanisms of how therapeutic mAbs elicit ADA are not completely clear. Accurate ADA detection is also necessary to provide clinicians with sufficient information for patient monitoring and clinical intervention, and several immunoassays for ADA detection have been developed. However, ADA assays present unique challenges because both the analyte and antigen are antibodies, so most assays are cumbersome, costly, time consuming, and lack standardization. This review will cover several aspects related to ADA formation resulting from mAb administration. First, we will provide an overview of the current prevalence of ADA formation and the available diagnostic tools for their detection. Next, we will review studies that support possible molecular mechanisms involved in the formation of ADA. Finally, we will present approaches aiming to decrease the propensity of mAbs to induce ADA.